Elisha: The Holy Man of God - Shemesh, Yael (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
Unlike Elijah's stories, Elisha's, especially the short legends, have received little scholarly attention or deep analysis. Though this is changing, recent research often views them as critical of Elisha. This book aims to highlight their richness and complexity through literary analysis and to establish them as the earliest example in Israelite literature of Saint's legends or prophetic hagiography